2012
DOI: 10.1111/j.1365-2230.2012.04338.x
|View full text |Cite
|
Sign up to set email alerts
|

Excision biopsy in a patient with suspected local anaesthetic allergy: use of 0.9% saline with benzyl alcohol as local anaesthesia

Abstract: Dermatologists may see patients with actual or suspected local anaesthetic (LA) allergy who require an urgent dermatological procedure to be performed without time for formal allergy testing. We report a case of shave biopsy and subsequent excision biopsy of an atypical naevus performed using tumescent analgesia with 0.9% saline containing benzyl alcohol preservative. The tumescence itself and the benzyl alcohol present in the 0.9% saline solution provided sufficient analgesia for excision. This technique may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The authors concluded that PS with 1:100,000 epinephrine offers prolonged cutaneous local anaesthesia with less pain than BL1E and offers a good alternative option, especially if patients are allergic to lidocaine. Joliffe and Sinclair [ 31 ] report using PS successfully for an excision biopsy of an atypical forearm naevus in a patient with a previous adverse reaction to local anaesthetic. Lugo-Janer et al [ 32 ] undertook a multi-phase study with phase one very similar to Wilson and Martin [ 30 ], involving volar forearm injections and pinprick testing up to 60 m post-injection [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The authors concluded that PS with 1:100,000 epinephrine offers prolonged cutaneous local anaesthesia with less pain than BL1E and offers a good alternative option, especially if patients are allergic to lidocaine. Joliffe and Sinclair [ 31 ] report using PS successfully for an excision biopsy of an atypical forearm naevus in a patient with a previous adverse reaction to local anaesthetic. Lugo-Janer et al [ 32 ] undertook a multi-phase study with phase one very similar to Wilson and Martin [ 30 ], involving volar forearm injections and pinprick testing up to 60 m post-injection [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…2 In addition, 0.9% saline with benzyl alcohol preservative ("bacteriostatic saline") has been used for tumescent anesthesia for both shave and excision biopsies in dermatologic patients with known or suspected allergy to LA. 3 Tumescent infiltration also allows for the administration of higher doses of lidocaine and epinephrine leading to longer-lasting anesthesia across a larger area with less blood loss. 4 This has been used effectively in burns patients undergoing surgical procedures 4 and was found to shorten the surgery duration, reduce postoperative pain, and lessen the development of ecchymosis and erythema in blepharoplasty surgery.…”
mentioning
confidence: 99%